(untitled) (SAIM Journal of Social Science and Technology, 2025)
Purpose: This study aims to identify key factors influencing Nepalese visitors’ adoption of STTs and to explore how STT use across other sectors impacts tourism, focusing on travel satisfaction and revisit intentions. Design, Methodology, and Approach: An explanatory study design was employed to examine the influence of STT attributes on travel satisfaction and revisit intention in Kathmandu Valley. Data were collected via structured surveys using Google Forms from 406 respondents, selected through non-probability sampling. Data analysis was conducted with Excel and SmartPLS 4. Findings: Results indicate that accessibility has minimal impact, while travel happiness, interactivity, personalization, and informativeness strongly affect visitors’ intention to revisit. Tourist satisfaction with STT experiences is a major determinant of continued use. Practical Implications: Enhancing positive STT experiences can boost visitor satisfaction and return rates. However, challenges such as outdated information and poor internet connectivity hinder adoption. Originality: This study contributes novel insights into STT adoption and its effects on travel behavior in Nepal’s tourism market, addressing a gap in regional research.